Disquisiciones autoriales en Fe de vida de Dulce María Loyna - Jiménez, Luis A. (2015)
In Fe de vida, by Cuban writer Dulce María Loynaz, we notice an authoritative dispositionof the biographical discourse. In the textual practice, writing and reading are articulated to the right of the author to publish the manuscript.